Studies on stub-loaded resonator for multi-mode microwave filters - Zou, Han. (2012)
The digital and microwave technologies developed really fast in recent decades. The ultra-wideband (UWB) technology turns into a hot topic and its potential applications would be very broad in the future. It needs to be pointed out that the UWB bandwidth for both indoor and outdoor communication systems is strictly regulated to 3.1GHz to 10.6GHz by Federal Communication Commission (FCC). Therefore the development of UWB band pass filter that is able to cover the whole UWB passband is highly demand. This project aims to study and design a bandpass filter for UWB applications through two design approaches: Short-circuited Microstrip Multiple-Mode Resonator (MMR) Filter Design and Slot-Line Embedded Design for UWB Bandpass Filter.